Streptomyces as a promising biological control agents for plant pathogens - Khan, Shaista; Srivastava, Seweta; Karnwal, Arun; Malik, Tabarak (Frontiers in Microbiology, 2023)
Plant diseases caused by pathogenic microorganisms in agriculture present a considerable obstacle, resulting in approximately 30-40% crop damage. The use of conventional techniques to manage these microorganisms, i.e., applying chemical pesticides and antimicrobials, has been discovered to have adverse effects on human health and the environment. Furthermore, these methods have contributed to the emergence of resistance among phytopathogens. Consequently, it has become imperative to investigate natural alternatives to address this issue. The Streptomyces genus of gram-positive bacteria is a potentially viable natural alternative that has been extensively researched due to its capacity to generate diverse antimicrobial compounds, such as metabolites and organic compounds. Scientists globally use diverse approaches and methodologies to extract new bioactive compounds from these bacteria. The efficacy of bioactive compounds in mitigating various phytopathogens that pose a significant threat to crops and plants has been demonstrated. Hence, the Streptomyces genus exhibits potential as a biological control agent for combating plant pathogens. This review article aims to provide further insight into the Streptomyces genus as a source of antimicrobial compounds that can potentially be a biological control against plant pathogens. The investigation of various bioactive compounds synthesized by this genus can enhance our comprehension of their prospective utilization in agriculture.